2021
DOI: 10.1186/s12886-021-02045-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of premyopia and myopia in Chinese preschool children: a longitudinal cohort

Abstract: Backgrounds Myopia has become a global public health problem. Children with early onset of myopia are at particular risk of complications associated with myopia. Younger children and children with greater initial myopic refractive errors are at a greater risk of myopia progression. Therefore, it is essential to identify subjects at high risk of developing myopia to facilitate myopia prevention in the early stage, especially during the preschool period. The purpose of this study was to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
2
16
1
Order By: Relevance
“…However, we found that in patients with cbEGF-like mutations, the total corneal K1 increased with aging (r s = 0.294, p = 0.038). This differs from the overall findings for MFS patients with lens subluxation ( Chen et al, 2018a ) or healthy children ( He et al, 2021 ; Liu et al, 2021 ), indicating the specific role of cbEGF-like mutations, rather than general FBN1 mutations, in age-related corneal changes.…”
Section: Discussioncontrasting
confidence: 84%
“…However, we found that in patients with cbEGF-like mutations, the total corneal K1 increased with aging (r s = 0.294, p = 0.038). This differs from the overall findings for MFS patients with lens subluxation ( Chen et al, 2018a ) or healthy children ( He et al, 2021 ; Liu et al, 2021 ), indicating the specific role of cbEGF-like mutations, rather than general FBN1 mutations, in age-related corneal changes.…”
Section: Discussioncontrasting
confidence: 84%
“…However, some studies found no association between height and refraction in preschoolers 17,24,25 ,which is consistent with our study. It can be easily understood that taller and heavier children have longer AL but atter cornea, thus resulting in a slight difference in refraction in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Axial length growth is associated with MS and myopia, ( 25 ) and a longer AL can be used to identify those at high risk of myopia in both pre-school and school-aged children ( 26 , 27 ). However, in our study, a longer pre-operative AL led to a slower MS in children with congenital/developmental cataracts with pseudophakic eyes.…”
Section: Discussionmentioning
confidence: 99%